(C6H13NH3)2(NH2CHNH2)Pb2I7: A Two‐dimensional Bilayer Inorganic–Organic Hybrid Perovskite Showing Photodetecting Behavior. Issue 9 (28th March 2019) - Wang, Yuyin; Liu, Xitao; Li, Lina; Ji, Chengmin; Sun, Zhihua; Han, Shiguo; Tao, Kewen; Luo, Junhua
Abstract: Inorganic–organic hybrid perovskites, especially two‐dimensional (2D) layered halide perovskites, have attracted significant attention due to their unique structures and attractive optoelectronic properties, which open up a great opportunity for next‐generation photosensitive devices. Herein, we report a new 2D bilayered inorganic–organic hybrid perovskite, (C6 H13 NH3 )2 (NH2 CHNH2 )Pb2 I7 (HFA, where C6 H13 NH3 + is hexylaminium and NH2 CHNH2 + is formamidinium), which exhibits a remarkable photoresponse under broadband light illumination. Structural characterizations demonstrate that the 2D perovskite structure ofHFA is constructed by alternant stacking of inorganic lead iodide bilayered sheets and organic hexylaminium layers. Optical absorbance measurements combined with density functional theory (DFT) calculations suggest thatHFA is a direct band gap semiconductor with a narrow band gap ( E g ) of ≈2.02 eV. Based on these findings, photodetectors based onHFA crystal wafer are fabricated, which exhibit fascinating optoelectronic properties including large on/off current ratios (over 10 3 ), fast response speeds ( τ rise =310 μs and τ decay =520 μs) and high responsivity (≈0.95 mA W −1 ). This work will contribute to the design and development of new two‐dimensional bilayer inorganic–organic hybrid perovskites for high‐performance photosensitive devices. Abstract : A good photoresponse : A new 2D bilayered inorganic–organic hybrid perovskite, (C6 H13 NH3 )2 (NH2 CHNH2 )Pb2 I7 (HFA, where C6 H13 NH3 + is hexylaminium and NH2 CHNH2 + is formamidinium), was synthesized, which exhibits a remarkable photoresponse under broadband light illumination. Structural characterizations demonstrate that the 2D perovskite structure ofHFA is constructed by alternant stacking of inorganic lead iodide bilayered sheets and organic hexylaminium layers.